2011
DOI: 10.1101/gad.2041611
|View full text |Cite
|
Sign up to set email alerts
|

The Dbp5 cycle at the nuclear pore complex during mRNA export I: dbp5 mutants with defects in RNA binding and ATP hydrolysis define key steps for Nup159 and Gle1

Abstract: Nuclear export of messenger RNA (mRNA) occurs by translocation of mRNA/protein complexes (mRNPs) through nuclear pore complexes (NPCs). The DEAD-box protein Dbp5 mediates export by triggering removal of mRNP proteins in a spatially controlled manner. This requires Dbp5 interaction with Nup159 in NPC cytoplasmic filaments and activation of Dbp5's ATPase activity by Gle1 bound to inositol hexakisphosphate (IP 6 ). However, the precise sequence of events within this mechanism has not been fully defined. Here we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
143
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(159 citation statements)
references
References 60 publications
5
143
0
1
Order By: Relevance
“…In the accompanying study (Hodge et al 2011), we found that such mutants behave as predicted. Notably, the ATP hydrolysis-defective dbp5 EQ mutant, which binds to either ATP or ADP ( Fig.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…In the accompanying study (Hodge et al 2011), we found that such mutants behave as predicted. Notably, the ATP hydrolysis-defective dbp5 EQ mutant, which binds to either ATP or ADP ( Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Notably, the ATP hydrolysis-defective dbp5 EQ mutant, which binds to either ATP or ADP ( Fig. 2A,B), is a loss-of-function mutant in vivo (Hodge et al 2011). Further, at steady state in the presence of wild-type Dbp5, dbp5 EQ protein is not detected at the nuclear rim/NPC (Hodge et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2b), elements required for ATP binding and hydrolysis, respectively 21,22 . As FRH is essential for the viability of Neurospora 7 , we expressed mutant and WT versions of FLAG-tagged FRH in an frh þ background.…”
Section: Resultsmentioning
confidence: 99%
“…Binding of Nup159 blocks the RNA-binding site of Dbp5 (REFS 17,121) (FIG. 5) and this is required for the release of ADP, adding a new level of DEAD box protein regulation by partner proteins 123,124 . So far, such an ADP-release factor has not been described for any other DEAD box protein, but it may not be unique to Dbp5.…”
Section: Nuclear Specklesmentioning
confidence: 99%